Effect of Sasobit warm mix on micro properties of asphalt with different degrees of regeneration - Tong, Bin; Song, Xuyan; Shen, Junan; Jiang, Ting; Chen, Jiafan; Niu, Junfeng (Frontiers in Materials, 2022)
In this work, an aged asphalt was obtained by simulating aging in the laboratory. Then, it was mixed with a new modified asphalt based on styrene-butadiene-styrene (SBS) in different proportions, and the warm mixing agent was added to simulate the asphalt fusion behaviour in the warm mixed recycled asphalt with different aged asphalt fertilizer (reclaimed asphalt pavement, RAP) content. Low field nuclear magnetic resonance (LF-NMR), atomic force microscopy (AFM) and Fourier transform infrared spectroscopy (FTIR) were used as analytical techniques to study the role of warm mixing agent in terms of molecular bond energy, apparent morphology and functional groups. It was found that the viscosity reduction effect of Sasobit warm mix agent is mainly realized by reducing the bond energy between 1H and other molecules. In the two-dimensional adhesion diagram, the number of bee-structures and single area is reduced. Therefore, Sasobit warm mix agent can improve the aging state of mixed asphalt. For the new and aged mixed asphalt, the greater the proportion of new asphalt, the better the effect of Sasobit warm mix agent.